AHP 1:A RESPONSE TO WAYS AND THE SYNTAX OF NOUN PHRASES IN QĪNGHĂI CHINESE DIALECTS - Keith, Dede (Asian Highlands Perspectives, 2018)
In the course of offering a review of Zhāng Chéngcái's Ways, this paper describes the syntax of noun phrases in the Chinese dialect of Huángshuĭ, in Qīnghăi Province. Unlike other Chinese dialects, this dialect employs several postpositions for indicating syntactic nominal relationships. The origin of this phenomenon in contact with non-Sinitic languages in the region and its significance are also explored.